Intersystem crossing rates of single perylene molecules in ortho-dichlorobenzene. Issue 26 (16th June 2016) - Verhart, Nico R.; Navarro, Pedro; Faez, Sanli; Orrit, Michel
Abstract : Triplet states can be interesting for optical switching of molecular fluorescence as well as quantum experiments relying on the manipulation of spin states. Abstract : Triplet states can be interesting for optical switching of molecular fluorescence as well as quantum experiments relying on the manipulation of spin states. However, the ground state of molecules is usually a singlet state. It is therefore interesting to study the intersystem crossing (ISC) rates between singlet and triplet states. We have measured the autocorrelation function of the fluorescence from single perylene molecules in an ortho -dichlorobenzene host matrix at cryogenic temperatures (1.3 K). We observed two time scales in the autocorrelation function corresponding to intersystem crossing to two indistinguishable triplet states (TX and TY ) and a third triplet state (TZ ). By studying the power dependence of the correlation times and contrasts in the autocorrelation functions of single molecules, we determine the ISC rates of perylene for the first time.